2020
DOI: 10.1152/jn.00433.2019
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous spinal cord stimulation of the cervical cord modulates lumbar networks

Abstract: It has been established that coordinated arm and leg (A&L) cycling facilitates corticospinal drive and modulation of cervico-lumbar connectivity and ultimately improves overground walking in people with incomplete spinal cord injury or stroke. This study examined the effect of noninvasive transcutaneous spinal cord stimulation (tSCS) on the modulation of cervico-lumbar connectivity. Thirteen neurologically intact adults participated in the study. The excitability of the Hoffmann (H) reflex elicited in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 64 publications
(45 reference statements)
0
22
0
Order By: Relevance
“…Enhancing cervico-lumbar connectivity by pairing A&L cycling with tSCS may further improve mobility outcomes (Pradarelli et al, 2020). Recently, we showed that cervical tSCS significantly suppresses the soleus H-reflex (the remote limb) (Barss et al, 2019), similarly to the effect of arm cycling on the soleus H-reflex. Benavides and colleagues showed that after 20 min of tSCS, the amplitude of subcortical MEP (i.e., cervicomedullary evoked potentials or CMEP) increased, but not the amplitude of MEPs (Benavides et al, 2020).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Enhancing cervico-lumbar connectivity by pairing A&L cycling with tSCS may further improve mobility outcomes (Pradarelli et al, 2020). Recently, we showed that cervical tSCS significantly suppresses the soleus H-reflex (the remote limb) (Barss et al, 2019), similarly to the effect of arm cycling on the soleus H-reflex. Benavides and colleagues showed that after 20 min of tSCS, the amplitude of subcortical MEP (i.e., cervicomedullary evoked potentials or CMEP) increased, but not the amplitude of MEPs (Benavides et al, 2020).…”
Section: Introductionmentioning
confidence: 87%
“…It may be possible that non-invasive spinal stimulation activates the spinal motor pools by increasing sensory inputs through Ia afferents (Sayenko et al, 2019). Our previous investigation determined that tonic activation of the cervical region through tSCS suppresses the amplitude of the soleus H-reflex (Barss et al, 2019) to a similar extent as that produced by rhythmic arm cycling (Zhou et al, 2018b), indicating that tSCS may also engage propriospinal interneuronal connections exerting effects on multiple segments of the spinal cord. Therefore, it was tempting to assume this suppressive effect would be bidirectional: tonic activation of the lumbar networks of the spinal cord by tSCS would reduce the amplitude of the H-reflex in FCR similarly to the suppressive effect rhythmic leg cycling has on the FCR H-reflex.…”
Section: Tscs Alters Excitability Of Remote Segments Of the Spinal Cordmentioning
confidence: 97%
See 2 more Smart Citations
“…A recent study by Barss et al emphasize the significant impact of percutaneous stimulation on the improvement of cervical-lumbar connectivity of the spinal cord, which is one of the goals of rehabilitation procedures in patients with spinal cord injury. It is reported that both the rhythmic activation of the cervical spinal cord by cyclic arm movements, with the use of specially adapted ergometers, and the tonic activation of the cervical spinal cord by tSCS significantly modulate the activity of the lumbar neural networks [27]. This action may also lead to the improvement of locomotor functions, mainly walking [5,27].…”
Section: Transcutaneous Spinal Cord Stimulationmentioning
confidence: 99%